Analyzing the Use of E-Voting Indonesian Election In 2024 - Indrawan, Jerry; Suprayitno, Dede (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2024)
The implementation of general elections in Indonesia poses various challenges, due to the form of an archipelagic country. The aspect of the region with its isolated, lagging, and remote character makes the election process require large resources, ranging from manpower, time and costs. To overcome this, the e-voting option emerged as an alternative to answer these challenges. The development of increasingly better technology makes the implementation of e-voting not impossible. The background of this study is based on the proposal to make elections in Indonesia less expensive. The purpose of the study is to determine whether the use of e-voting is suitable for implementation in Indonesia. The research method uses qualitative with research sources derived from primary and secondary data. The main result of this study is that e-voting can be considered for use in future elections. The author's conclusion is that e-voting is very possible to be implemented in Indonesia. However, the government needs to answer a number of needs. Among others, such as network infrastructure, data security, and readiness of human resources to remote areas.